Conjunto de características para teste de desempenho: uma visão a partir de modelos - Silveira, Maicon Bernardino da (2012)
Software testing process has a high cost when compared to the other stages of software development. Automation of software testing through reuse of software artifacts (e.g. models) is a good alternative for mitigating these costs and making the process much more efficient and effective. In this sense, the Model-Based Testing (MBT) approach has increased in Software Engineering. MBT is a technique of automatic generation of testing artifacts based on software models, which also includes the specification of the aspects to be tested. This work aims to study techniques and methodologies for MBT and to evaluate the features of the different models applied in MBT. The main contribution of this study is to analyze the features of the models that are used in performance testing of web applications. In another perspective, it presents an approach for generating test cases based on FSM (Finite State Machines). Furthermore, it describes the process of generating the test cases using the HSI method (Harmonized State Identification). Besides, the implementation of a plug-in in the PLeTs tool based on UML SPT profile, which interprets the set of features designed for performance testing, is presented in a real case study. Our work, defines which features must be present in a model when modeling user interactions with a SUT (System Under Test). This will allow the increasing in automation and in reusing testing artifacts throughout the systems development life cycle. Furthermore, our solution is generated automatically by a Software Product Line (SPL).